PENGARUH MANAJERIAL PIMPINAN, SISTEM INFORMASI KEPEGAWAIAN DAN IKLIM ORGANISASI TERHADAP PRODUKTIVITAS KERJA DOSEN PADA SEKOLAH TINGGI ILMU TARBIYAH ( STIT ) AL – HIKMAH TEBING TINGGI - Nurul Akbar Syahfitri; Ferawati Ferawati; Herman Sakti Siregar; Bukhari Bukhari; Neneng Mariana (Manajemen dan Bisnis, 2022)
The formulation of the problem in this study is whether the supervision, work environment and The formulation of the problem in this study is: How is the influence of managerial leadership, personnel information systems and organizational climate on lecturers' work productivity. This study aims to determine the effect of managerial leadership, information systems personnel and organizational climate on the productivity of professors. With the total sampling technique samples in this study as many as 56 people. Managerial leadership partially has a positive effect on lecturers' work productivity; The information system partially has a positive effect on lecturers' work productivity; Organizational climate partially has a positive effect on lecturers' work productivity; Managerial leadership, information systems and organizational climate have a positive and positive effect on lecturers' work productivity.